SOLUBILITY ISOTHERM OF MANGANESE SULFATE - MONOETHANOLAMINE - WATER AT 10ºC (Academicia Globe: Inderscience Research, 2022)
Novel Imine were prepared via the reaction of (p-chloro and p-methyl)aniline with (p-nitro and p-methoxy) benzaldehyde and later engaged in a condensation reaction with 2-O-Acetylmalic anhydride in a dioxane as a solvent. The resulting products were found to be 1,3-oxazepine-1,5-diones and their derivatives. FT-IR , 1HNMR and C.H.N. spectra were used to confirm the structures of  products. The antibacterial properties of these compounds were also examined.